REPRESENTATIONS OF MESSIANISM IN 19 TH CENTURY JAVANESE SOCIETY IN INDONESIAN NOVELS SET DURING THE JAVAN WAR(1825-1830) - Budiyanto, Dwi (Prosiding Konferensi Internasional Kesusasteraan, 2025)
The history of resistance by wong cilik (the common people), especially in the nineteenth and early twentieth centuries, against colonialism was often driven by a belief in the coming of a Javanese messiah. This was the case during the Java War (1825-1830). Messianism was often depicted as a mystical figure with diverse beliefs, including when the messiah was presented in literary texts. This study aims to describe the representation of messianism in nineteenth-century Javanese society in Indonesian novels set during the Java War (1825-1830). The data consists of story facts, including the storyline, characters, setting, themes, and other literary devices from data sources that contain information related to the research objectives. The data was obtained through reading and note-taking techniques. The data sources were selected purposively, namely Indonesian novels set during the Java War that represent the messianism of 19th-century Javanese society, namely (1) Pangeran Diponegoro: Menggagas Ratu Adil (2007) and (2) Pangeran Diponegoro: Menuju Sosok Khalifah (2008) by Remy Sylado. The data was then analyzed qualitatively from a new historicism perspective. The results of the study reveal that the messianism of Javanese society in Indonesian novels is represented as follows. (1) Nineteenth-century Javanese messianism was formed between a belief in mystical prophecies and logical leadership education. (2) Javanese messianism was born from the Javanese people's belief in the presence of the Ratu Adil (Just King) as well as the concept of a caliph on earth. The two are not contradictory, but are represented as integral concepts. The resistance against colonialism driven by the concept of Javanese messianism articulates the community's hopes for change.